A glycogen branching enzyme from Thermomonospora curvata: Characterization and its action on maize starch. (2nd November 2015) - Fan, Qin; Xie, Zhengjun; Zhan, Jinling; Chen, Hailong; Tian, Yaoqi
Abstract : A gene ( TcGBE ) encoding a glycogen branching enzyme from Thermomonospora curvata was expressed in Escherichia coli and purified, and biochemically analyzed. The purified enzyme was approximately 84 kDa, and exhibited a maximum activity at 55°C and pH 8.5. The enzyme showed the highest specificity to amylose with a specific activity of 90.28 U/mg. The recombinant enzyme could act on maize starch, and starch treated with TcGBE was observed to have a lower amylose content and molecular weight. The number of short chains of amylopectin in TcGBE‐modified starch with a degree of polymerization (DP) less than 13 increased from 20.19 to 32.59%, and was accompanied by a reduction in longer chains (DP > 25) from 25.58 to 10.03%. In addition, the medium length chains of amylopectin (13 < DP <25) also showed a slight increase from 54.23 to 58.38%. The 1 H NMR spectra revealed an increased ratio of α‐1, 6‐ to α‐1, 4‐glucosidic linkages from 4.1 to 10.3% following treatment with TcGBE for 10 h. Taken together, these results suggested that TcGBE could be used to generate a modified maize starch with a low amylose content and more branched amylopectin of low molecular weight but richer in short and intermediate chains.